Yeast-Based Genetic System for Functional Analysis of Poxvirus mRNA Cap Methyltransferase - Saha, Nayanendu (American Society for Microbiology, 2003)
Structural differences between poxvirus and human mRNA capping enzymes recommend cap formation as a target for antipoxviral drug discovery. Genetic and pharmacologic analysis of the poxvirus capping enzymes requires in vivo assays in which the readout depends on the capacity of the viral enzyme to catalyze cap synthesis. Here we have used the budding yeast Saccharomyces cerevisiae as a genetic model for the study of poxvirus cap guanine-N7 methyltransferase. The S. cerevisiae capping system consists of separate triphosphatase (Cet1), guanylyltransferase (Ceg1), and methyltransferase (Abd1) components. All three activities are essential for cell growth. We report that the methyltransferase domain of vaccinia virus capping enzyme (composed of catalytic vD1-C and stimulatory vD12 subunits) can function in lieu of yeast Abd1. Coexpression of both vaccinia virus subunits is required for complementation of the growth of abd1Δ cells. Previously described mutations of vD1-C and vD12 that eliminate or reduce methyltransferase activity in vitro either abolish abd1Δ complementation or elicit conditional growth defects. We have used the yeast complementation assay as the primary screen in a new round of alanine scanning of the catalytic subunit. We thereby identified several new amino acids that are critical for cap methylation activity in vivo. Studies of recombinant proteins show that the lethal vD1-C mutations do not preclude heterodimerization with vD12 but either eliminate or reduce cap methyltransferase activity in vitro.